Plasmonic Metasurface Resonators to Enhance Terahertz Magnetic Fields for High‐Frequency Electron Paramagnetic Resonance. Issue 9 (29th July 2021) - Tesi, Lorenzo; Bloos, Dominik; Hrtoň, Martin; Beneš, Adam; Hentschel, Mario; Kern, Michal; Leavesley, Alisa; Hillenbrand, Rainer; Křápek, Vlastimil; Šikola, Tomáš; van Slageren, Joris
Abstract: Nanoscale magnetic systems play a decisive role in areas ranging from biology to spintronics. Although, in principle, THz electron paramagnetic resonance (EPR) provides high‐resolution access to their properties, lack of sensitivity has precluded realizing this potential. To resolve this issue, the principle of plasmonic enhancement of electromagnetic fields that is used in electric dipole spectroscopies with great success is exploited, and a new type of resonators for the enhancement of THz magnetic fields in a microscopic volume is proposed. A resonator composed of an array of diabolo antennas with a back‐reflecting mirror is designed and fabricated. Simulations and THz EPR measurements demonstrate a 30‐fold signal increase for thin film samples. This enhancement factor increases to a theoretical value of 7500 for samples confined to the active region of the antennas. These findings open the door to the elucidation of fundamental processes in nanoscale samples, including junctions in spintronic devices or biological membranes. Abstract : Plasmonic metasurfaces are versatile structures able to manipulate electromagnetic fields beyond natural possibilities. Their application can be extended to magnetic resonance techniques working at terahertz frequencies. This provides a series of significant and unprecedented advantages in terms of sensitivity and integrability when dealing with nanosized materials as well as ultra‐thin molecular films.